RELATION OF CONSCIOUSNESS WITH EXISTENT AS A BASIS OF ONTOLOGICAL UNDERSTANDING - Yakup KAHRAMAN (Fırat University, 2019)
The ability of revealing the truth itself without getting need mediation and the idea is the most significant approach of modern philosophy. This approach assumed that consciousness gets universal, timeless and absolute knowledge with its own abilities and could not notice the change of consciousness within life and the effect of this change on our comprehension experiment. However, existent has an important impact on the shape of consciousness. Hegel is one of the most important philosophers who included that impact in his philosophical thought he generated in history of philosophy and wanted to comprehend the consciousness within the dialectic process. Hegel has tried to show the change of consciousness by building between the existent and dialogical axis in his philosophy of consciousness. His approach coincides with the assumption that ontological understanding existed in dialogical and historical axis. In this study it is tried to reveal ontological understanding in philosophy of consciousness Hegel suggested against philosophers such as Descartes and Kant who generates epistemology by situating consciousness in transcendental position.